Current status and future trends of eco-friendly management of postharvest fungal decays in tomato fruit - Zhenshuo Wang; Mumian Wu; Qinhong Liao; Yawen Wang; Yuan Sui; Chao Gong (npj Science of Food)
Abstract This article reviews sustainable strategies to control postharvest fungal decay (e.g., Botrytis cinerea, Alternaria spp., and Colletotrichum gloeosporioide) in tomato. Eco-friendly alternatives to synthetic fungicides, focusing on microbial antagonists, and integrated approaches combining biological control with natural compounds, are discussed. Emerging technologies like microbial consortia, nanomaterials, and CRISPR/Cas9 show great potential, though further research and regulatory approval are required. These sustainable methods are crucial for maintaining tomato quality and yield while supporting environmentally responsible production.